Low Back Pain, Ergonomics and Ayurveda - A Clinical Insight (AYUSHDHARA, 2025)
Low back pain (LBP) is a major cause of global disability, with most cases being non-specific and influenced by physical, psychosocial, and lifestyle factors. Conventional approaches involving physiotherapy and NSAIDs often yield limited outcomes, emphasising the need for individualised, holistic care. This review integrates modern ergonomic principles with Ayurvedic concepts to establish a comprehensive framework for LBP prevention and management. Methodology: Data were compiled from classical Ayurvedic texts and biomedical literature in databases such as PubMed and Google Scholar. The review synthesised evidence on the prevalence, aetiology, and management of LBP, with particular focus on ergonomics and Ayurvedic interventions. Keywords included “Low Back Pain and Ayurveda,” “Ergonomics and Ayurveda,” and “Musculoskeletal Disorders and Preventive Strategies.” Occupational health scenarios were also analysed to merge theoretical and clinical insights. Review Results: LBP, often corresponding to Ayurvedic Vata Vyadhi conditions like Gridhrasi, Katigraha, and Katishoola, arises mainly from biomechanical strain and poor ergonomics. Prolonged static postures and repetitive movements exacerbate Vata imbalance. Modern ergonomic strategies, such as adjustable workstations and posture retraining, directly mitigate these factors. Complementary Ayurvedic therapies, such as Basti (medicated enema), Snehana (oleation), Swedana (sudation), and herbal formulations like Trayodashanga Guggulu, restore Doshic equilibrium and strengthen tissues. An integrative model that unites ergonomic optimisation with Ayurvedic therapies shows promise for sustainable relief and recurrence prevention. Conclusion: Integrating ergonomic principles with Ayurvedic management offers a patient-centred strategy that addresses both biomechanical and physiological dimensions of LBP. Future multi-centric randomised trials are needed to validate and standardise this integrative approach.